A Rare Case: Adenocarcinoma Bronchogenic Dextra Std IVB on Gefitinib (15 months) accompanied by Decreased Visual Acuity, Bilateral Sensorineural Deafness and Psychiatric Disorders with No Radiological Evidence of Brain Metastasis - Ensang Timuda, Caesar; Dwi Pratiwi, Suryanti; Rahmawati, Dessika; Yudhantara, Dearisa; Erawati, Dini; Indrasworo, Dyah; Prayitnaningsih, Seskoati (Universitaas Brawijaya, 2022)
Background: Leptomeningeal disease occurs in 3-5% of patients with lung cancer, mainly adenocarcinoma subtype. Adenocarcinoma is the most common histological finding in Asian women. Case: A 51-year-old woman with right-sided bronchogenic adenocarcinoma T4N3M1c Std IVB mutation(+) developed decreased vision, severe bilateral sensorineural deafness and psychiatric disorders after receiving Gefitinib 15 months. There was no evidence of brain metastasis from brain MRI. From evaluation of chest CT-scan, we found the disease was progressive and no Mutation Detected from ctDNA, so Gefitinib was discontinued. Conclusion: We found some difficulties in evaluating side effects of therapy and disease progression due to patient's condition in the form of decreased total vision, severe sensorineural deafness, and psychiatric disorders. However, because no radiological evidence of brain metastases was found, we suspect this patient suffered from leptomeningeal disease. Keywords: Lung Cancer, Adenocarcinoma, Gefitinib, Leptomeningeal Disease